PENGARUH LATIHAN SPIDERMAN CRAWL TERHADAP KELENTURAN OTOT TUNGKAI PADA PEMAIN SEPAKBOLA SISWA EKSTRAKURIKULER SMPNEGERI 1 CERENTI KABUPATEN KUANTAN SINGINGI - Menrofa, Julius; Wijayanti, Ni Putu Nita; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based the observation, the student used to get low score for the flexibility of leg muscle in playing football. It was shown when they did dribbling or the other techniques. The aim of the research was to know the effect of spiderman crawl to the leg muscle flexibility in playing football for the extracurriculer students of SMP 1 Cerenti in Kuantan Singingi. The population was the extracurriculer students of SMP 1 Cerenti in Kuantan Singingi 2013 / 2014 which was 24 students. Based on the population, the collecting data was total sampling which the researcher took whole population as the samples. The instrument of the research was front splits test. The data were analysed by using T-test. According to T-test, rcount 3.236 and ttable 1.714 so Ha was refused in alpha level ( α ) 0.05. It was concluded that there was the effect of spiderman crawl training through the leg muscle flexibily in playing football for the extracurriculer students of SMPN 1 Cirenti Kuansing.Keywords : Spiderman crawl training, the leg muscle flexibility.